2021
DOI: 10.1037/prj0000501
|View full text |Cite
|
Sign up to set email alerts
|

Crisis event dispositions following a crisis response team intervention.

Abstract: Objective: We examined dispositions of crisis response team (CRT) events over 2 years in a large Midwestern city. Method: Between January 1, 2018 and December 31, 2019, the CRT self-dispatched to mental/behavioral health-related 9-1-1 calls. Data utilized for analysis included demographic information of persons in crisis, crisis type, and crisis event dispositions. Crisis types were mental health, self-harm, and substance use related. Event dispositions included immediate detention, arrest, transport, and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…This is an introduction to the special section "Recovery-Oriented Care in Acute Care and Crisis Service Settings." Please see the without stable housing, while Bailey et al (2021) found persons experiencing homelessness were more likely to be arrested than those who are not. Clearly, even recovery-oriented services such as these struggle to support the recovery of persons experiencing homelessness.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…This is an introduction to the special section "Recovery-Oriented Care in Acute Care and Crisis Service Settings." Please see the without stable housing, while Bailey et al (2021) found persons experiencing homelessness were more likely to be arrested than those who are not. Clearly, even recovery-oriented services such as these struggle to support the recovery of persons experiencing homelessness.…”
mentioning
confidence: 99%
“…In this special section, Bailey et al (2021) report on one of many promising alternative approaches to criminal justice response to mental health crises—crisis response teams (CRTs). While prior trials have shown CRTs to be promising in reducing arrest of persons referred for mental health crisis, their study further elucidates factors associated with disposition at the scene.…”
mentioning
confidence: 99%
See 2 more Smart Citations